Dermoscopic findings in female androgenetic alopecia Achados dermatoscópicos na alopecia androgenética feminina - Lya Duarte Ramos; Maria Cândida Nahás Santili; Fabiane Castilho Bezerra; Maria de Fátima Maklouf Amorim Ruiz; Valeria Petri; Marisa Teresinha Patriarca (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: Androgenetic alopecia is the most common form of hair loss. It is a clinical entity of relevant interest and presents a significant psychosocial impact as it undermines self-esteem and quality of life in female patients due to the importance of the hair for people's facial balance. OBJECTIVE: The purpose of the present study is to evaluate dermoscopic signs in women clinically diagnosed with androgenetic alopecia. METHOD: Observational study with 34 women between 17 and 68 years old who were diagnosed with androgenetic alopecia. All of them underwent photographic sessions with a 10x magnification dermoscope and a digital camera zoom set to 20x magnification and 40x magnification on the scalp frontal midline. RESULTS: All patients showed miniaturization. A peripilar brown halo was found in 22 patients, honeycomb-like scalp pigmentation was found in 14 and yellow dots in only 1 patient. Recent studies show dermoscopy as the new tool for diagnosis assistance and treatment follow up in scalp disorders. Our study used an ordinary dermoscope and we evaluated several findings reported in the literature with significant clarity and easiness. CONCLUSION: The dermoscope, which is used by dermatologists on a daily basis, is an excellent tool to assist in early diagnosis and assessment of therapeutic response in androgenetic alopecia. FUNDAMENTOS: Alopecia androgenética é forma mais comum de queda de cabelo. Constitui entidade clínica de interesse relevante e acarreta grande impacto psicossocial por comprometer a auto-estima e a qualidade de vida das pacientes. OBJETIVO: Procurar os sinais dermatoscópicos comuns em mulheres com diagnóstico clínico de alopecia androgenética, visando diagnóstico precoce e melhor resposta terapêutica. MÉTODOS: Estudo observacional em 34 mulheres com idades entre 17 e 68 anos, com diagnóstico clínico de alopecia androgenética. Todas pacientes foram avaliadas e submetidas a registros fotográficos com o dermatoscópio no aumento de 10x e câmera digital no aumento de 20x e 40x na linha média frontal do couro cabeludo. RESULTADOS: Todas as pacientes apresentaram miniaturização dos fios na área examinada. Halo castanho peripilar foi encontrado em 22 pacientes, pigmentação em favo de mel em 14 e pontos amarelos em apenas 1 paciente. Estudos recentes mostram a dermatoscopia como uma nova ferramenta no auxílio diagnóstico e acompanhamento do tratamento das desordens do couro cabeludo. Em nosso estudo utilizamos um dermatoscópio comum e avaliamos vários achados relatados na literatura com facilidade e clareza significativas. CONCLUSÃO: O dermatoscópio, instrumento de uso diário dos dermatologistas, é excelente ferramenta para auxílio no diagnóstico precoce e avaliação da resposta terapêutica na alopecia androgenética e é capaz de mostrar de forma simples sinais precoces de miniaturização capilar.